Comunidades eclesiais de base na história social da igreja: Cariacica (1973-1989) - Barbosa, Fabiane Machado (2007)
The Basic Ecclesial Comunities (BECs) has an important contribution to the Catholic Church. These communities appear in the 60´s and express a ´new way of being catholic´, representing with actions a new trying to decentralize the old structure of that institution. From its organization in small groups, the BECs articulated efficiently the relationship between faith and politics and helped to take place an importation popular movement of organization and claim with remarkable influence on the fights for the democratization of the Brazilian society against the despotism of the military force. In the Church of Vitória, these communities were especially stronger, because, just before the organization of them the rule of the Catholic was nothing but giving total support to the dominant groups. During the eighties the democratization of Brazilian society open many new ways of participation. The Church began to change its ideology, starting to argue that each part of society has its own responsibility in it. The Church become again only a spiritual home and all the politic movements left the institution. In this work we describe the birth, the development and the regress to spiritual issues as a priority in the BECs.